STRATEGI GURU DALAM MENGINTEGRASIKAN NILAI-NILAI PANCASILA DALAM PEMBELAJARAN IPA UNTUK MEMBENTUK KARAKTER SISWA DI KELAS IV SDN 181 TANJUNG JABUNG BARAT - Elfia, Asih; Syahran, M.; Wiratama , Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the integration of Pancasila values in science (IPA) learning to shape student character in Grade IV at SDN 181 Tanjung Jabung Barat. Globalization challenges and limited rural infrastructure that undermine students' moral values motivated this research. A qualitative descriptive approach with a case study design was employed, with data collected through interviews, participant observation, and lesson plan documentation, validated through triangulation, and analyzed using the Miles and Huberman model. Findings reveal the teacher applies heterogeneous group discussions and simple practicums using local materials to cultivate values corresponding to Pancasila's 2nd (humanity), 3rd (unity), and 5th (justice) principles. Obstacles include inadequate laboratory facilities, frequent power outages, and limited internet access. This strategy proves effective in developing student character, and the study recommends teacher training and parental collaboration for sustained character development.